Synthesis and Thermal Behaviour of Co(II), Ni(II) and Cu(II) Complexes of N,N-di-n-propyl-N?- (2-chlorobenzoyl)thiourea - BINZET, G_N; Arslan, HAKAN; KULCU, NEVZAT (Asian Journal of Chemistry, 2010)
The Co(II), Ni(II) and Cu(II) complexes of N,N-di-n-propyl-N′-(2- chlorobenzoyl)thiourea were synthesized and the thermal behaviour of all complexes was studied by differential thermal analysis and thermal gravimetry methods. A GC-MS combined system was used to identify the decomposition products. The pyrolytic end products were identified by X-ray powder diffraction method. Both nickel and copper complexes decomposed in three stages, but cobalt complex decomposed in two stages. End products of the decomposition reactions were identified as Ni3S2, Co4S3 and Cu1.96S. The decomposition of the complexes begins with breakage the longer metal-oxygen bond in chelate ring, since these complexes decompose at higher temperatures proportional to 1/metal-ligand bond length.